Summary of the FESAC Transformative Enabling Capabilities Panel Report. (3rd April 2019) - Maingi, R.; Lumsdaine, A.; Allain, J. P.; Chacon, L.; Gourlay, S. A.; Greenfield, C. M.; Hughes, J. W.; Humphreys, D.; Izzo, V.; McLean, H.; Menard, J. E.; Merrill, B.; et al.
Abstract: The U.S. Fusion Energy Sciences Advisory Committee was charged "to identify the most promising transformative enabling capabilities (TEC) for the U.S. to pursue that could promote efficient advance toward fusion energy, building on burning plasma science and technology." A subcommittee of U.S. technical experts was formed and received community input in the form of white papers and presentations on the charge questions. The subcommittee identified four "most promising transformative enabling capabilities": 1. advanced algorithms 2. high critical temperature superconductors 3. advanced materials and manufacturing 4. novel technologies for tritium fuel cycle control. In addition, one second-tier TEC, defined as a "promising transformative enabling capability, " was identified: fast-flowing liquid-metal plasma-facing components. Each of these TECs presents a tremendous opportunity to accelerate fusion science and technology toward power production. Dedicated investment in these TECs for fusion systems is needed to capitalize on the rapid advances being made for a variety of nonfusion applications to fully realize their transformative potential for fusion energy.